EDUKASI GIZI DAN PELATIHAN PENGOLAHAN IKAN BANDENG DALAM UPAYA PENCEGAHAN STUNTING - Simamora, Gevbry Ranti Ramadhani (Buletin Udayana Mengabdi; Vol 24 No 3 (2025): Buletin Udayana Mengabdi, 2024)
Stunting is a chronic problem caused by prolonged malnutrition, starting from pregnancy to early postnatal phase. In 2022, the prevalence of stunting cases in Balikpapan City reached 19.6%, increased from the previous 17%, ranking it ninth out of 10 cities in East Kalimantan Province. The impact of stunting can persist into adulthood. Efforts to prevent the increase of stunting cases in Balikpapan can be done by providing education about the importance of stunting prevention through consumption of local foods, such as milkfish. The aim of this activity is to enhance the understanding and skills of the community in utilizing local foods to improve child nutrition and prevent stunting. This community service approach utilizes knowledge transfer methods and direct practice in training sessions, as well as simulations in product creation competitions. The success of the activity is evaluated by comparing pre-test and post-test scores. The results of the community service provided to the Posyandu mothers demonstrate an increase in knowledge, understanding, and skills of the community in preventing stunting.   Keywords: Baby, Local, Nugget, Food, Local, Knowledge.